A new sympagic nematode species Daptonema gelida sp. n. (Monhysterida, Xyalidae) from the White Sea landfast ice - Timchenko, Anna I.; Portnova, Daria A. (Zootaxa, 2024)
A new ice-associated species of Xyalidae family, Daptonema gelida sp. n., is described from the first-year fast sea ice of the Ermolinskaya Inlet, White Sea, Russia. The new species of Daptonema is a morphologically distinct species from other species of the genus. Daptonema gelida sp. n. is characterized by (1) elongated, slender body, (2) short, evenly distributed throughout the body somatic setae, (3) circular amphideal fovea, (4) thin and strongly curved, L-shaped spicules with round-shaped manubrium, (5) gubernaculum with short dorsal-caudal apophysis by triangular-shaped outline, (6) post-vulval uterine sac present, and (7) two short terminal setae. We barcoded partial 18S rRNA gene sequences from the new sympagic species. Phylogenetic reconstructions showed that the specimen of Daptonema gelida sp. n. formed a distinct lineage with high support among other Daptonema species and was genetically related to D. carnulentum, D. setosum, D. hirsutum, Metadesmolaimus sp. and Daptonema spp. We provided a list of valid Daptonema species, including key morphological characteristics of males, and additionally reviewed 30 species inquirenda.